Towards a theoretical approach to national systems of innovation - Benavente, José Miguel; Crespi, Gustavo (Estudios de Economía, 2016)
The purpose of this paper is to formulate a theoretical framework as an alternative to the neoclassical one in order to find a more consistent explanation to the phenomenon of innovation and the process of growth. This new frame of thought, developed on the axis of the Schumpeterian process of competition and on learning as a social phenomenon, is characterized by the systemic nature of the interactions between agents and institutions. It is posited here that such interactions can be characterized by four key processes, namely: technological absorption, human capital formation, transformation (and creation of new endogenous technology) and technological diffusion. The latter is related to informational channels which allow connecting the former three processes in the most efficient manner possible. Though some of these channels operate through the markets, the process governing most of them is characterized by the existence of strong imperfections which generates a need for public intervention and calls for the creation of institutions to solve them.